Unpacking teacher decision-making: Connecting complex elements - Trevisan, Ottavia; Phillips, Michael; De Rossi, Marina (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2021)
Teaching is a complex endeavor requiring countless decisions to be made, sometimes within the blink of an eye. The recent outbreak of emergency remote teaching due to the pandemic emphasized the importance of teachers' expert knowledge in supporting deep learning online. Even though various attempts have been made in the literature, a comprehensive understanding of how knowledge, skills, epistemology, and values affect teacher reasoning and actions remains elusive. While acknowledging the role of single factors, this paper advocates a systemic view of teacher decision-making in technology rich contexts. An Epistemic Frame is suggested as a way of systemically integrate epistemology, skills, values, and knowledge peculiar to the teacher community. Introducing Quantitative Ethnography and Epistemic Network Analysis, this paper argues that the connections among elements of teachers' epistemic frames are pivotal, and thus calls for research methodologies that facilitate the explicit modelling of such connections. To this end, two studies will be introduced as examples.